Antifungal Activity of Ellagic Acid In Vitro and In Vivo. (28th April 2015) - Li, Zhi‐Jian; Guo, Xin; Dawuti, Gulina; Aibai, Silafu
<x xml:space="preserve">Abstract</x> Ellagic acid (EA) has been shown to have antioxidant, antibacterial, and anti‐inflammatory activities. In Uighur traditional medicine, Euphorbia humifusa Willd is used to treat fungal diseases, and recent studies suggest that it is the EA content which is responsible for its therapeutic effect. However, the effects of EA on antifungal activity have not yet been reported. This study aimed to investigate the inhibitory effect of EA on fungal strains both in vitro and in vivo. The minimal inhibitory concentration (MIC) was determined by the National Committee for Clinical Laboratory Standards (M38‐A and M27‐A2) standard method in vitro. EA had a broad spectrum of antifungal activity, with MICs for all the tested dermatophyte strains between 18.75 and 58.33 µg/ml. EA was also active against two Candida strains, with MICs between 25.0 and 75.0 µg/ml. It was inactive against Candida glabrata. The susceptibility of six species of dermatophytes to EA was comparable with that of the commercial antifungal, fluconazole. The most sensitive filamentous species was Trichophyton rubrum (MIC = 18.75 µg/ml). Studies on the mechanism of action using an HPLC‐based assay and an enzyme linked immunosorbent assay showed that EA inhibited ergosterol biosynthesis and reduced the activity of sterol 14α‐demethylase P450 (CYP51) in the Trichophyton rubrum membrane, respectively. An in vivo test demonstrated that topical administration of EA (4.0 and 8.0 mg/cm2) significantly enhanced the cure rate in a guinea‐pig infection model of Trichophyton rubrum. The results suggest that EA has the potential to be developed as a natural antifungal agent. Copyright © 2015 John Wiley & Sons, Ltd.